Pengaruh Organizational Learning Culture Terhadap Employee Performance Dengan Job Satisfaction Sebagai Mediasi - Evelyn Angelina; Yanuar Yanuar (Jurnal Manajerial Dan Kewirausahaan, 2021)
This study aims to determine the role of job satisfaction in mediating the relationship between organizational learning culture and employee performance. The subjects studied were the employees at PT XYZ which is an import agent company as well as a complete supplier of factory doors and warehouse needs in Indonesia. The number of samples taken in this study were 85 employees and 15 supervisors who were obtained by distributing questionnaires through google form with Non-probability sampling technique. The collected data is processed using SmartPLS. The results of data processing indicate that organizational learning culture has a positive effect on job satisfaction, job satisfaction has a positive effect on employee performance. However, the function of job satisfaction as a mediating variable in this study was not achieved because the correlation value with mediation is smaller than the value of organizational learning culture which can directly have a positive effect on employee performance. So the employee performance in this study is a partial mediation. Penelitian ini bertujuan untuk mengetahui Peranan Kepuasan Kerja sebagai Mediasi Hubungan antara Budaya Belajar Organisasi dan Kinerja Karyawan. Subjek yang diteliti adalah karyawan pada PT XYZ yang merupakan perusahaan agen import serta penyedia pintu pabrik dan kebutuhan gudang secara lengkap di Indonesia. Jumlah sampel yang diambil pada penelitian ini adalah karyawan dengan jumlah 85 orang dan supervisor 15 orang yang diperoleh dengan menyebar kuesioner melalui google form dengan teknik pengambilan sampel jenuh/sensus. Data yang telah dikumpulkan diolah menggunakan SmartPLS. Hasil dari pengolahan data menunjukkan bahwa budaya belajar organisasi berpengaruh positif terhadap kepuasan kerja, kepuasan kerja berpengaruh positif terhadap kinerja karyawan. Namun, fungsi kepuasan kerja sebagai variabel mediasi pada penelitian ini tidak tercapai karena nilai kolerasi dengan adanya mediasi lebih kecil daripada nilai budaya belajar organisasi yang secara langsung dapat berpengaruh positif terhadap kinerja karyawan. Maka kinerja karyawan disini merupakan mediasi parsial.